2021
DOI: 10.2147/ijn.s317409
|View full text |Cite
|
Sign up to set email alerts
|

Potential Privilege of Maltodextrin-α-Tocopherol Nano-Micelles in Seizing Tacrolimus Renal Toxicity, Managing Rheumatoid Arthritis and Accelerating Bone Regeneration

Abstract: Background: Tacrolimus (TAC) is a powerful immunosuppressive agent whose therapeutic applicability is confined owing to its systemic side effects. Objective: Herein, we harnessed a natural polymer based bioconjugate composed of maltodextrin and α-tocopherol (MD-α-TOC) to encapsulate TAC as an attempt to overcome its biological limitations while enhancing its therapeutic anti-rheumatic efficacy. Methods: The designed TAC loaded maltodextrin-α-tocopherol nano-micelles (TAC@MDα-TOC) were assessed for their physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…The micelles have been found to show stronger anti-rheumatic effects than the free drug. In vitro and in vivo experiments have demonstrated that TAC@MD-α-TOC is more effective than the free drug in promoting the viability of Vero cells and decreasing the levels of IL-6 and TNF-α in the serum and synovial fluid [68]. Monotherapy with MTX usually leads to irreversible joint injury because of its slow onset and long duration.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…The micelles have been found to show stronger anti-rheumatic effects than the free drug. In vitro and in vivo experiments have demonstrated that TAC@MD-α-TOC is more effective than the free drug in promoting the viability of Vero cells and decreasing the levels of IL-6 and TNF-α in the serum and synovial fluid [68]. Monotherapy with MTX usually leads to irreversible joint injury because of its slow onset and long duration.…”
Section: Polymeric Micellesmentioning
confidence: 99%